Educational poverty in Italy: concepts, measures and policies - Gian Luca Battilocchi (Debrecen University Press, 2020)
In recent years in Italy, as a result of the initiative by the NGO Save the Children Italia and of the government action, we have witnessed the success of the notion of "povertà educativa", as an effective way to indicate severe inequalities in education across the country. Firstly, the aim of this paper is to shed light on the different concepts and measures of educational poverty in socio-economic literature, in order to highlight specific and innovative aspects of this idea. Moreover, the paper intends to scrutinize Save the Children's proposal in order to monitor and tackle educational poverty as well as to show how the action of the NGO has influenced the development of Italian recent government policies against child and educational poverty.